A opção preferencial pelos pobres nas conferências gerais do CELAM - Pietranera, Fernando Glucklich (2019)
This paper aims to present the understanding of the poor at the Latin American and Caribbean Episcopal Conferences (CELAM). The purpose is to analyze whether, in each of the five Conferences that were held, there was an evolution of thinking about the poor in the theology and in the conclusions of the CELAM documents. In the Conferences of the Episcopate there is clearly the concern of the Latin American Church for the person and his reality, in all that constitutes the fabric of human life, its difficulties, anxieties, dramas and scourges. The see-judge-act method is clearly present, enabling the analysis and conclusions that the Church needed to present to society on the subject. At each conference, the Church updated the needs of the people. And so, he sought answers in the light of the Gospel so that each person could be protagonist of his existence and the Church would be present in this world of Latin America.